Analisis Kandungan Logam Berat Timbal (Pb) dan Tembaga (Cu) pada Anadara Granosa di Perairan Dusun Selangan Kota Bontang - Fatmy Yaumil Akhir Jafar; Fitri Noerhidayanti; Fitriyana Fitriyana; Iwan Suyatna (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study examines the impact of industrial activities in Bontang City, a major center for natural gas processing and fertilizer production, which potentially increases heavy metal contamination in coastal waters. Specifically, the research focuses on the accumulation of lead (Pb) and copper (Cu) in Anadara granosa, a benthic bivalve selected as a bioindicator due to its capacity to accumulate pollutants. The study aims to analyze Pb and Cu concentrations in Anadara granosa tissues collected from the waters of Selangan Hamlet, Bontang City, as an indicator of local environmental quality. The research was conducted over a six-month period, involving shellfish and water sampling from four observation stations. Heavy metal analysis was performed using Atomic Absorption Spectrophotometry, and the results were evaluated against relevant environmental quality standards, including Government Regulation of the Republic of Indonesia Number 22 of 2021. The findings revealed the presence of Pb and Cu at all sampling stations, with varying concentrations. The highest Pb and Cu levels were recorded at the South Station, while the lowest concentrations were observed at the East and North Stations. Overall, the measured concentrations of both metals significantly exceeded established safety limits, indicating serious risks to aquatic ecosystems and human health. These results confirm Anadara granosa as an effective bioindicator of heavy metal pollution and highlight the urgent need for further studies and mitigation efforts.